The Psychometric Properties of the Arabic Preschool Activity Card Sort - Somaya H. Malkawi; Sana M. N. Abu-Dahab; Ahmad F. Amro; Nihad A. Almasri (Occupational Therapy International)
Background. The Preschool Activity Card Sort (PACS) is an interview-based assessment tool to measure participation of preschool children with age range from 3 to 6 years. Objective of Study. The purpose of this study was to establish the psychometric properties of the recently translated Arabic PACS (A-PACS). Methods. One hundred fifty-one Jordanian parents participated in the study representing different geographical areas. Children were almost equally distributed between males and females and into three age groups. Construct and concurrent validity were examined as well as the internal consistency of the scale and the test-retest reliability. Findings. The A-PACS was able to differentiate between the participation level of young and old children in the domains of education, community mobility, and low demand leisure of the A-PACS giving evidence to its construct validity and it significantly correlated with some aspects of the Vineland Adaptive Behavior Scale (VABS) giving evidence to its concurrent validity. The A-PACS showed excellent overall internal consistency (α=.859) for all domains and good test-retest reliability (r=.976, p<.001). Conclusion. The A-PACS can be considered as a valid and reliable tool to measure participation of preschool children with normal development from Arabic cultures. Future studies should focus on the validity of the A-PACS for use with children with disabilities.